DVR based reactive power control strategy of DFIG for wind energy generation during unbalanced grid voltages - Geethanjali, S.; Shanmugapriya, S. (International Journal of Engineering and Technology, 2017)
This document offers a whole new one on direct power control (DPC) technique for a doubly fed induction generator (DFIG)-based the wind vitality era program. This tactic relies on the one on one supervision regarding system productive and reactive strength by simply deciding on applicable voltage vectors on the rotor feature. This strategy works by using the mechanical system flux that take away the complications linked to rotor flux. This guidelines with this strategy rectangular calculate delineated intimately with this document. The one unit parameter needed by the projected DPC technique is usually which the mechanical system resistance as their effect on the system effectiveness is located to get minimal. Simulation final results on the 1.5 MW DFIG program exhibits the effectiveness and robustness in the projected supervision tactic in the course of versions regarding unit details. DVR is usually given to management the facility excellent issues and thereby management the active and reactive power.